Pemanfaatan Metode PECS (Picture Exchange Communication System) untuk Meningkatkan Pemahaman Instruksi Dua Langkah pada Peserta Didik Autis Spektrum Disorder - Pinky Agustin, Madeline; Kinanthi , Morula; Mauliya; Ananda , Eka; Ardianingsih, Febrita; Wahyudi, Zahra Ajid Berlianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the use of the Picture Exchange Communication System (PECS) method to enhance the understanding of two-step instructions among learners with Autism Spectrum Disorder (ASD). The aim of this research is to provide a comprehensive explanation of the application of PECS as a method to improve communication skills and the ability to follow two-step instructions in children diagnosed with ASD. A descriptive qualitative approach was employed, with data collected through direct observation, interviews, and documentation at Sonokwijenan II/96 Surabaya State Elementary School. The results indicate that the use of PECS is effective in improving students’ ability to comprehend sequential two-step instructions and express their needs.